The Effect of Credit Risk Management on Finanacial Perforamance of Financial Institutions - Dulukansi Naluwooza (Uganda Christian University, 2023)
ABSTRACT The purpose of the study was to establish the effect of credit risk management on financial performance of financial institutions. The study had three objectives; to examine the effect of credit risk analysis on financial performance of financial institutions, to examine the effect of credit risk monitoring on financial performance of financial institutions and to examine the effect of credit risk mitigation on financial performance of financial institutions. The study used a case of Finca Micro Finance Mityana Branch. A cross sectional survey research design where quantitative data was collected at only one point in time. The required primary data was collected directly from the respondents through administering a structured questionnaire. The study had a population 100 elements with a sample size 0f 86 elements which also formed the unit of inquiry of 69 respondents. The researcher used SSPS for data entry and analysis. Data analysis was quantitative in nature and it was expressed in percentages to present the findings. The results indicated credit risk management has a significant positive influence on the financial performance of financial institution. The respondent agreed that credit risk monitoring reduce the number of none performing loans which can be faced by the institutions. In addition, respondents also agreed that financial institutions conduct credit risk monitoring practices such record keeping after they have extended loans to their clients which positively affected their financial performance. Furthermore, the respondents also agreed that credit risk mitigation reduce the number of non-performing thus positively affecting the financial performance of these institutions therefore it should be properly implemented with a well-established department or team that is responsible an Answerable to every concern related to credit risk mitigation.
This is a dissertation.